2019
DOI: 10.1590/1808-1657000182019
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interaction and economic injury level of Urochloa plantaginea in corn hybrids

Abstract: Identifying the competitive ability of corn hybrids and the economic injury level (EIL) caused by Urochloa plantaginea is important for the adoption of integrated management of this weed. This work aims to evaluate the interference and EIL of U. plantaginea infesting corn hybrids. Treatments included the corn hybrids Syngenta Status VIP3, Syngenta SX8394 VIP3, Pioneer P1630H, Pioneer 30F53 YH, and Dow 135021, as well as 12 densities of U. plantaginea for each hybrid. We used a rectangular hyperbolic model to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 19 publications
6
17
0
Order By: Relevance
“…In addition to the loss of control efficiency by herbicides to which the weed has resistance (HEAP, 2020), the coexistence of this weed with maize can cause serious losses due to its high competitiveness, as shown in the present study. This work confirms the results found by Vazin (2012), Wandscheer et al (2014), Frandoloso et al (2019; Galon et al (2019) and Galon et al (2021) when they denote that competition occurred between corn grown in the presence of slender amaranth, sudangrass, plantain alexandergrass, crabgrass and morningglory, respectively. Research has reported that species belonging to botanical families, with similar or different characteristics, have similarities in the demand for resources in the environment; cultivated sorghum x Sorghum halepense (HOFFMAN; BUHLER, 2002), rice x redrice (FLECK et al, 2008), maize x crabgrass and morningglory (GALON et al, 2021), maize x plantain alexandergrass (FRANDOLOSO et al, 2019;GALON et al, 2019), maize x sudangrass (WANDSCHEER; RIZZARDI; REICHERT, 2013), rice and soybean x crabgrass (AGOSTINETTO et al, 2013) and soybean x radish (BIANCHI; FLECK; LAMEGO, 2006).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition to the loss of control efficiency by herbicides to which the weed has resistance (HEAP, 2020), the coexistence of this weed with maize can cause serious losses due to its high competitiveness, as shown in the present study. This work confirms the results found by Vazin (2012), Wandscheer et al (2014), Frandoloso et al (2019; Galon et al (2019) and Galon et al (2021) when they denote that competition occurred between corn grown in the presence of slender amaranth, sudangrass, plantain alexandergrass, crabgrass and morningglory, respectively. Research has reported that species belonging to botanical families, with similar or different characteristics, have similarities in the demand for resources in the environment; cultivated sorghum x Sorghum halepense (HOFFMAN; BUHLER, 2002), rice x redrice (FLECK et al, 2008), maize x crabgrass and morningglory (GALON et al, 2021), maize x plantain alexandergrass (FRANDOLOSO et al, 2019;GALON et al, 2019), maize x sudangrass (WANDSCHEER; RIZZARDI; REICHERT, 2013), rice and soybean x crabgrass (AGOSTINETTO et al, 2013) and soybean x radish (BIANCHI; FLECK; LAMEGO, 2006).…”
Section: Resultssupporting
confidence: 90%
“…This work confirms the results found by Vazin (2012), Wandscheer et al (2014), Frandoloso et al (2019; Galon et al (2019) and Galon et al (2021) when they denote that competition occurred between corn grown in the presence of slender amaranth, sudangrass, plantain alexandergrass, crabgrass and morningglory, respectively. Research has reported that species belonging to botanical families, with similar or different characteristics, have similarities in the demand for resources in the environment; cultivated sorghum x Sorghum halepense (HOFFMAN; BUHLER, 2002), rice x redrice (FLECK et al, 2008), maize x crabgrass and morningglory (GALON et al, 2021), maize x plantain alexandergrass (FRANDOLOSO et al, 2019;GALON et al, 2019), maize x sudangrass (WANDSCHEER; RIZZARDI; REICHERT, 2013), rice and soybean x crabgrass (AGOSTINETTO et al, 2013) and soybean x radish (BIANCHI; FLECK; LAMEGO, 2006). The knowledge of dynamics and competitiveness between plants, especially maize and wild poinsettia, becomes important for the decision to control the weed in a certain population that will not cause negative interference on the crop.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, when volunteer plants occur at lower densities, adopting measures to control them becomes difficult, as farmers need to quantify the economic benefits associated with the control cost (Galon et al, 2019). Thus, it is necessary to implement management strategies that integrate technical knowledge and economic analysis with the competitive relationship between crops and weeds (Westwood et al, 2018).…”
Section: High Densities Of Plants Competing With Cropsmentioning
confidence: 99%
“…Thus, it is an excellent alternative to manage weeds when cultivated in succession to summer crops, such as maize, soybean, and common bean (18,32). Furthermore, there is strong evidence of differences in competitive ability among both varieties of the same crop and among distinct genotypes of wild species (3,19).…”
Section: Introductionmentioning
confidence: 99%